Strength Properties of Polymer Reactive Powder Concrete with Waste Materials - Shatha Sadiq Hasan; Mohammed Y. Fattah (Salehan Institute of Higher Education, 2023)
Reactive powder concrete, or RPC, outperforms conventional or even high-performance concrete in terms of ultra-high strength and better durability. Several buildings were destroyed in Iraq, and recycling the garbage from these buildings can significantly help reduce waste and environmental pollution as well as serve as a source of aggregate for use in new construction. Reusing garbage and using sustainable building materials are now crucial environmental challenges, so this study aimed to replace the natural fine aggregate, NFA, used in preparations of polymer reactive powder concreter,